Activated-Constituents in the Rhizomes and Roots of Rheum tanguticum - Liu, Juan; Liu, Chun-Sheng; Wang, Qiu-Ling; Zhang, Yuan; Wang, Wen-Quan; Cheng, Xiao-Li; Guo, Zheng-Zheng; Wei, Sheng-Li (Asian Journal of Chemistry, 2014)
The rhizomes and roots of Rheum tanguticum are both used as rhubarb, a traditional Chinese medicine (TCM) in China. The activated-constituents, including free anthraquinones, anthraquinone glycosides, dianthrones, flavan-3-ols and hydrolyzable tannins were determined in the aforementioned two medicinal parts by RP-HPLC technique. The results showed the contents of the activated constituents in the roots were generally higher than those in rhizomes, meaning maybe that the medicinal quality of the roots of rhubarb is superior to the rhizomes. These observations do not support the traditional views.